Clinical observation of docetaxel or gemcitabine combined with cisplatin in the chemotherapy after surgery for stage II–III non-small cell lung cancer - Chen, Qiu-Qiang; Ji, Xue-Xian; Zhou, Xiao; Shi, Qi-Lin; Yu, Huan-Ming; Fu, Heng-Qin; Ji, Guo-Ping (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : This study aimed to compare the efficacy and toxicity of docetaxel combined with cisplatin (DP) and gemcitabine combined with cisplatin (GP) in postoperative chemotherapy after surgery of non-small cell lung cancer (NSCLC). Material and methods: A total of 92 patients diagnosed with NSCLC after surgery were enrolled, and they were treated with DP (DP group) and GP (GP group). The efficacy and toxicity of the medications were then compared. Results: Approximately 92.4% (85 out of 92) of the patients received chemotherapy for more than three weeks. In the DP and GP groups, the incidence rates of grade III–IV thrombocytopenia were 24.4% and 6.38%, respectively, whereas the incidence rates of alopecia were 88.9% and 25.5%, respectively. The difference between the two groups was statistically significant (p 0.05). Conclusions : These results showed similar disease-free survival rates of DP and GP therapies in one and two years after surgery for NSCLC. However, the DP group exhibited higher incidence rates of grade III–IV thrombocytopenia and alopecia than the GP group. Therefore, we should select a specific treatment for each patient according to individual differences.